AUTONOMOUS ONLINE READING USING PQRST TO ENHANCE THE STUDENTS READING SKILL IN RECOUNT TEXT - Enik Evi Indahwati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
The lack of maximum reading competency achieved by students becomes the background of this research. Data of the students reading competency score on descriptive text shows the average of 70.19 which is still far below the minimum standard score of 77. Literature review shows several factors influencing the low level of student reading competencies, namely: (1) minimum vocabulary mastery, (2) the absence of reading strategies used which results in difficulties to understand long sentences, (3) lack of background knowledge, and (4) less motivated to learn English because of the monotonous teaching methods. By using Classroom action Research, this study aims at improving the students reading skills of recount text by employing autonomous online reading using PQRST technique. The results of the study show that (1) the students scores in reading were significantly increased, (2) the students activity in class in learning activities was increased, and (3) students comprehension of the recount text was facilitated by the PQRST strategy by activating their background knolwledge (Preview), writing what they want to know (Question), Readingand Summarizing the text, then continued by Test. In conclusion, autonomous online reading with PQRST techniques can improve student learning outcomes well.